Hvorfor stemmer de ikke guitarerne ordentligt i Dar es Salaam? Transskription, analyse og notation i musiketnologi - Kirkegaard, Annemette (Danish Yearbook of Musicology, 2000)
With a point of departure in contemporary African music, the present article discusses the problems of modern transcription. By addressing the two dichotomies of insider/outsider and local/global respectively, the ethnomusicological focus on transcription is examined and the use of mechanical aids is debated. The music of Dar es Salaam guitar bands and their relation to traditional musical systems is made an empirical example of the problems facing the modern transcriber, and the article ends by suggesting further research into the complicated and complex procedures of present-day analysis of creolised music cultures of the world.